Effects of Service Quality on Guest Satisfaction in Restaurants Business - Silwal, Bikash (Journal of Nepalese Management and Research, 2025)
Service excellence is the main reason for customer satisfaction in competitive hospitality sectors, especially in emerging economies like Nepal. Global studies confirm this, but there is little empirical research on Nepal’s dining industry, particularly in developing areas like Karnali Province. The study aims to find out the link between service quality and guest satisfaction in the restaurant business of Birendranagar, Surkhet. The main objective of the study is to analyze the five key dimensions of service quality, which are tangibility, reliability, assurance, responsiveness, and empathy, and their influence on consumer satisfaction in the restaurant sector. A quantitative approach for the research was adopted. A total of 406 people were surveyed through a structured questionnaire to collect the data. Then, correlation and regression analysis with SPSS was performed to evaluate the effect of each service dimension on overall satisfaction. The four dimensions such as tangibles, assurance, responsiveness, and empathy were found to have a significant positive association with guest satisfaction according to the analysis. On the other hand, reliability was not considered as a statistically significant predictor of satisfaction levels in this particular market. The results suggest that the main factors influencing customer satisfaction in restaurants at Birendranagar are the physical environment, staff skill and friendliness, quick service, and personal care. The result for reliability, which is not significant, shows that local enterprises need to work on maintaining consistent service. This study presents realistic recommendations for the owners of restaurants to tactically improve their service and thereby acquire a competitive edge.